2022
DOI: 10.1002/aur.2803
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prefrontal transcranial direct current stimulation (tDCS) on theory of mind, emotion regulation and emotional‐behavioral functions in children with autism disorder: A randomized, sham‐controlled, and parallel‐group study

Abstract: Advances in our knowledge about the neuropsychological mechanisms underlying core deficits in autism spectrum disorder (ASD) have produced several novel treatment modalities. One of these approaches is modulation of activity of the brain regions involved in ASD symptoms. This study examined the effects of transcranial direct current stimulation (tDCS) over the dorsolateral prefrontal cortex (DLPFC) on autism symptom severity, theory of mind, emotion regulation strategies, and emotional‐behavioral functions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 89 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…The intervention was safe, and only two adverse events occurred, including insomnia and irritability on the second night after tDCS in one case and feeling irritable all day in the evening of the second and third days after tDCS in the second case [58 && ]. In the next study, 10 sessions of anodal tDCS (1.5 mA, 15 min per session) in 32 children with autism resulted in no adverse event other than the common side effects during the stimulation and up to 1-month follow-up [59]. In another tDCS study conducted in 25 children with ADHD (12 sessions, 1 mA), the adverse effects were mild, but three children, all from the real tDCS group, experienced headaches, with two requiring temporary cessation and one requiring removal from the study [60].…”
Section: Andandmentioning
confidence: 84%
“…The intervention was safe, and only two adverse events occurred, including insomnia and irritability on the second night after tDCS in one case and feeling irritable all day in the evening of the second and third days after tDCS in the second case [58 && ]. In the next study, 10 sessions of anodal tDCS (1.5 mA, 15 min per session) in 32 children with autism resulted in no adverse event other than the common side effects during the stimulation and up to 1-month follow-up [59]. In another tDCS study conducted in 25 children with ADHD (12 sessions, 1 mA), the adverse effects were mild, but three children, all from the real tDCS group, experienced headaches, with two requiring temporary cessation and one requiring removal from the study [60].…”
Section: Andandmentioning
confidence: 84%
“…It is worth noting that “transcranial direct current stimulation”, “double blind” and “adolescent” have been the most active burst keywords since 2019. In the past two years, clinical research on tDCS has mainly been carried out in children and adolescents with autism, and has played a positive role in the recovery of social functions [ 66 , 68 , 102 ]. This may reflect future research trends to a certain extent and may be related to the clinical trials in the treatment of adolescent psychiatric disorders by tDCS.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that DBS in the ventral forelimb of the internal capsule or medial forebrain bundle could reduce the symptoms of obsessive–compulsive behavior and depression, which indicates that neuromodulation techniques may be an effective intervention in the comorbidity of ASD, but further exploration is needed [ 135 ]. In addition, we found that some recent clinical studies predominantly focused on the positive effects of tDCS in adolescents with ASD, including social cognition and emotional behavior [ 66 , 68 , 102 ]. Working memory is often impaired in ASD, which may be the basis of the core defects of cognitive and social functions [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…They observed superior effects of five and 20 sessions versus sham with the concurrent behavioral intervention, with no difference between 5 and 20 sessions (Auvichayapat & Auvichayapat, 2022). (Zemestani et al, 2022) conducted a randomized, sham‐controlled, and parallel‐group study of children 7–12 years old with ASD ( n = 17 and 15 in active and sham groups respectively). Participants received 10 sessions (15 min) of active or sham bilateral dlPFC (left anodal/right cathodal) stimulation over 5 weeks.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%